POTLATCH OR GENEROSITY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the Chinook language of the Native American Indians, the word “potlatch” means to feed, to consume. If a tribe or tribal leader wanted his wealth to be a talking point among the people for centuries, or if there was an important event to celebrate, he organized a potlatch and scattered his wealth. Potlatch was also held for various good and bad reasons. Potlatch was preserved in the Heiltsuk, Haida, Nuxalk, Tlingit, Makah, Tsimshian, Nuu-Chah-Nulth, Kwakwaka’wakw, Chinook, and Coast Salish tribes in the USA and Canada. This article will discuss the similarities and differences in the generosity of the indigenous tribes living in the USA and the Kyrgyzs.
Keywords: potlatch, generosity, Native Americans, Kyrgyzs.